2016
DOI: 10.1186/s13054-016-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

Early goal-directed therapy in severe sepsis and septic shock: insights and comparisons to ProCESS, ProMISe, and ARISE

Abstract: Prior to 2001 there was no standard for early management of severe sepsis and septic shock in the emergency department. In the presence of standard or usual care, the prevailing mortality was over 40-50 %. In response, a systems-based approach, similar to that in acute myocardial infarction, stroke and trauma, called early goal-directed therapy was compared to standard care and this clinical trial resulted in a significant mortality reduction. Since the publication of that trial, similar outcome benefits have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 196 publications
(132 reference statements)
4
94
0
5
Order By: Relevance
“…Examples of this include activated protein C and early goal-directed therapy for sepsis. 2,3 Results from other studies, such as the ARDSnet protocol, appear to have better stood the test of time. 4 But these interesting controversies lead to the crucial focal point of our discussion.…”
Section: Change As It Relates To the Evidencementioning
confidence: 99%
“…Examples of this include activated protein C and early goal-directed therapy for sepsis. 2,3 Results from other studies, such as the ARDSnet protocol, appear to have better stood the test of time. 4 But these interesting controversies lead to the crucial focal point of our discussion.…”
Section: Change As It Relates To the Evidencementioning
confidence: 99%
“…For example, PRISM investigators identified subgroups of severely sick patients, and the size of this sample was 4 times larger than the entire cohort studied by Rivers et al These investigators used eight ways to stratify the disease severity and identified the top third of predicted risk of death. However, they found no treatment benefit with EGDT in patients with greater severity of illness (8,9). This failure to replicate the results in the Rivers study suggests that current usual care treatment strategies can provide equal reductions in mortality.…”
Section: Hawa Edrissmentioning
confidence: 99%
“…As expected, patients in EGDT arm received the same interventions used in the EGDT protocol of the Rivers study. These three studies concluded that EGDT did not reduce the 90-day mortality in patients who received EGDT compared to usual care (8,9). Furthermore, EGDT was associated with increased admission to ICU and higher hospitalization costs across a wide range of patients and hospitals.…”
Section: Hawa Edrissmentioning
confidence: 99%
“…Because of methodological issues, several recent large multicenter studies failed to demonstrate a beneficial effect of EGDT as compared to usual care. Yet, the conceptual framework underlying EGDT is still considered as the cornerstone for the early management of sepsis and septic shock (7,8).…”
Section: Introductionmentioning
confidence: 99%